2022
DOI: 10.1007/s41999-022-00625-5
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and C-reactive protein relate to functional and body composition parameters in patients admitted to geriatric rehabilitation after acute hospitalization: findings from the RESORT cohort

Abstract: Purpose Albumin and C-reactive protein (CRP) are non-specific markers of inflammation, which could affect muscle tissue during acute hospitalization. We investigated the association between albumin and CRP during acute hospitalization with functional and body composition parameters in patients admitted to geriatric rehabilitation. Methods The REStORing Health of Acutely Unwell AdulTs (RESORT) cohort includes geriatric rehabilitation patients assessed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…[24,25] Recent studies showed that albumin and BMI are associated with body composition parameters. [26,27] In this study, BMI and albumin showed a possible correlation with skeletal muscle measurement. Therefore, BMI and albumin might be possible alternative indicators for estimating myopenia in patients who had not undergone an imaging study, but more research is needed to confirm this.…”
Section: Discussionsupporting
confidence: 57%
“…[24,25] Recent studies showed that albumin and BMI are associated with body composition parameters. [26,27] In this study, BMI and albumin showed a possible correlation with skeletal muscle measurement. Therefore, BMI and albumin might be possible alternative indicators for estimating myopenia in patients who had not undergone an imaging study, but more research is needed to confirm this.…”
Section: Discussionsupporting
confidence: 57%
“…When albumin falls below 35g/L, it indicates a state of malnutrition in patients. Sustaining higher levels of albumin contributes to the protection of the body, helping to mitigate physiological stress responses induced by inflammation [5]. Consequently, timely albumin supplementation postoperatively can effectively reduce the likelihood of postoperative fever in patients undergoing total hip arthroplasty (THA).Research by Lai HF et al [6] suggested that postoperative serum albumin levels below 32g/L are one of the contributing factors to postoperative fever.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ageing clocks may be useful for predicting recovery and adverse adaptations [3]. During hospitalization, individual biomarkers, such as albumin and C-reactive protein, can predict physical function [4], and composite biomarkers, such as the frailty index based on blood parameters, can predict mortality [5]. Similarly, higher biological age predicted by blood biomarkers denotes accelerated ageing rates, which is indicative of mortality [6,7] and a set of health conditions [8] in community-dwelling and hospitalized populations.…”
Section: Introductionmentioning
confidence: 99%